Prenatal diagnosis of orofacial clefts: unveiling the parents' experience - Verônica Aparecida Pezzato da Silva; Marina Gifalli; Francine Aroteia Capone; Francely Tineli Farinha; Priscila Capelato Prado; Armando dos Santos Trettene (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To understand the experience of parents regarding prenatal diagnosis of orofacial cleft in their children. Methods: Descriptive study with a qualitative approach, carried out in a Brazilian public tertiary hospital between January and March 2019. Parents who were accompanying their children during hospitalization for primary surgeries and who had received the diagnosis of malformation during pregnancy were included in this study. Data was collected through semi-structured interviews, which were audio-recorded and transcribed in full. To prepare the results, Content Analysis was used in the Thematic modality. Results: The sample had 17 participants: 16 mothers and one father. From the speeches, three categories were unveiled: dealing with the unknown, assimilating the diagnosis, and positive and negative implications of prenatal diagnosis. Conclusions: We learned how complex and conflicting it was for parents to receive the diagnosis of malformation in their children, and that family and professional support was essential to the process of assimilation and coping. The findings point to the need for planning and implementing interventions, protocols and/or public policies aimed at assisting these parents in this period.